Mastering your fellowship: Part 3, 2024 - Klaus B. von Pressentin; Ts'epo Motsohi; Gert Marincowitz; Tasleem Ras (South African Family Practice, 2024)
The series ‘Mastering your Fellowship’ provides examples of the question formats encountered in the written and clinical examinations, Part A of the Fellowship of the College of Family Physicians of South Africa (FCFP [SA]) examination. The series aims to help family medicine registrars (and supervisors) prepare for this examination.